Robust Ferromagnetism of Chromium Nanoparticles Formed in Superfluid Helium. Issue 1 (27th October 2016) - Yang, Shengfu; Feng, Cheng; Spence, Daniel; Al Hindawi, Aula M. A. A.; Latimer, Elspeth; Ellis, Andrew M.; Binns, Chris; Peddis, Davide; Dhesi, Sarnjeet S.; Zhang, Liying; Zhang, Yafei; Trohidou, Kalliopi N.; et al.
Abstract : Chromium nanoparticles are formed using superfluid helium droplets as the nanoreactors, which are strongly ferromagnetic. The transition from antiferromagentism to ferromagnetism is attributed to atomic‐scale disorder in chromium nanoparticles, leading to abundant unbalanced surface spins. Theoretical modeling confirms a frustrated aggregation process in superfluid helium due to the antiferromagnetic nature of chromium.